Strategic Planning and Organizational Performance: An Applied Study in Zawia University (Comprehensive Journal of Science, 2026)
This study aims to investigate the nature of the causal relationship between strategic planning (with its five dimensions: vision and mission, strategic goals and values, environmental analysis, projects and operational plans, and monitoring and evaluation) and organizational performance at the University of Zawia, within the context of unstable environmental transformations witnessed by Libyan educational institutions. The study adopted the descriptive analytical approach, and utilized a structured questionnaire as the primary tool for data collection from a purposive-random sample consisting of (80) academic and administrative staff members. Data were subjected to statistical analysis using SPSS v.28, through reliability tests (Cronbach's Alpha), Pearson Correlation coefficient, and Multiple Regression Analysis. The results revealed the existence of a positive, strong, and statistically significant correlation (at a significance level of α≤0.01) between strategic planning and organizational performance (r=0.74, p
Keywords: Strategic Planning, Organizational Performance, University of Zawia, Implementation Gap, Strategic Monitoring